(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The objective of this research is to ascertain the impact of variations in the drill method training on the jump serve ability of athletes from the Bina Putri Volleyball Club in 2025. The research method employed is quantitative, characterised by a one-group pre-test and post-test design. The subjects of this study are female athletes who actively participate in training at the club, with a total of 18 training sessions over a period of six weeks. The research instrument employed is a validated jump serve skill test, with measurements obtained through five trials in both the pre-test and post-test phases. The drill training provided includes variations in starting techniques, jumps, hits, and landings, which are practised repetitively and in a structured manner. The collected data is then subjected to a series of statistical tests, specifically paired t-tests, to ascertain the disparities between the outcomes observed in the preliminary and subsequent assessments. The analysis results indicate that the calculated t value of 4.46 is greater than the table t value of 1.83. This finding suggests that there is a significant effect of the variation of the drill method training on the improvement of jump serve ability. The present study offers empirical evidence that systematic and progressive drill training can enhance the fundamental technical skills in volleyball, particularly concerning the jumping serve.